METODE PEMBELAJARAN BAHASA INGGRIS ANAK USIA DINI - Iman Nurjaman; Titi Rachmi; Nurul Fitria KD; Angger Prima Widiasih; Nargis Nargis; Diah Retno Anggraini (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
This study aims to determine the knowledge of parents about early childhood English learning methods. The approach in this study uses qualitative using interview methods. the results of the study showed that of the 40 parents interviewed, 38 parents could mention the method used in learning English in early childhood while 2 parents could not mention an appropriate method for learning English in early childhood. methods that fit the characteristics and development of early childhood are conversation, playing, telling stories, singing, using pictures and playing roles.Keywords: early childhood English learning, learning methods, characteristics of early childhood